Polyyne rotaxanes - Movsisyan, L (2014)
This thesis describes the synthesis of polyyne rotaxanes and an investigation of their excited state photophysical properties. The threading of dumbbell-shaped carbon chains with macrocyclic components is a way to mechanically insulate and control the environment around the carbon chains. The resulting polyyne rotaxanes can serve as model compounds for insulated carbyne. Different strategies have been tested for the synthesis of polyyne rotaxanes with different topologies and structures. Study of rotaxanes in the excited states reveals strong electronic communication between an acetylenic thread and a macrocycle. Chapter 1 summarizes the field of acetylene scaffolding, introducing some recent achievements in acetylene chemistry. General synthetic methods for polyynes are discussed, and an introduction to active metal template synthesis of rotaxanes is given. Chapter 2 describes the synthesis of a family of polyyne rotaxanes with different axle lengths and macrocycles, prepared by homocoupling of terminal alkynes. Synthesis of hexayne rotaxane with functional pyridine end-group is presented and a number of crystal structures of polyyne rotaxanes are analyzed. Chapter 3 demonstrates the use of acetylene cross-coupling in the synthesis of rotaxanes. Synthesis of rotaxanes with different topological structure is provided. Chapter 4 details the excited state properties of polyynes studied by time -resolved spectroscopy. The complexes of rhenium(I) carbonyls with rotaxanes is presented and the excited state energy transfer in rotaxanes is studied. Chapter 5 explores new synthetic strategies for polyyne rotaxanes, using "masked" precursors. It also highlights the potential of carbenoid rearrangement of alkyliden es for the construction of linear and cyclic architectures. Chapter 6 is the summary of the project and general discussion of future directions. There are two appendices in the end of thesis: Appendix A covers the photophysics of rhenium tricarbonyl complex of the hexayne rotaxane with a small macrocycle and Appendix B reports work towards the synthesis of rotaxanes with platinum(II)-alkyne complexes.